Konvergensi dan Divergensi Penentuan Awal Waktu Asar dan Isya: Analisis Komparatif Imam 4 Mazhab - Yusuf Nasrul Wathon (CV Global Research Publication, 2025)
Prayer is a time-bound act of worship (muwaqqat) whose validity depends on its timely performance, which is determined by the position of the sun. This research examines the points of convergence and divergence in determining the start times for the Asr and Isha prayers according to the four major schools of Islamic jurisprudence: Hanafi, Maliki, Shafi'i, and Hanbali. Using a qualitative library research method with a descriptive-comparative approach, this study analyzes the roots of jurisprudential disagreement (ikhtilaf) in the methodology of interpreting evidence (istinbath al-hukm) and translates qualitative legal criteria into quantitative astronomical parameters. The results show that the divergence in Asr time is rooted in differing interpretations of hadith regarding the length of an object's shadow—one times its length (Jumhur/majority) versus two times (Hanafi). Meanwhile, the difference in Isha time stems from a lexical and juridical polemic over the definition of syafaq whether it refers to the red twilight (al-syafaq al-ahmar) or the white twilight (al-syafaq al-abyad). A computational analysis for Surabaya on April 1, 2022, reveals a significant time difference for Asr (approximately 62 minutes) and a more moderate difference for Isha (12 minutes), highlighting the practical implications of these jurisprudential distinctions.